Bioprinting 3D human cardiac tissue chips using the pin type printer 'microscopic painting device' and analysis for cardiotoxicity. (23rd February 2021) - Chikae, Shohei; Kubota, Akifumi; Nakamura, Haruka; Oda, Atsushi; Yamanaka, Akihiro; Akagi, Takami; Akashi, Mitsuru
Abstract: In this study, three-dimensional (3D) cardiac tissue constructed using the pin type bioprinter 'microscopic painting device' and layer-by-layer cell coating technique was confirmed to have drug responsiveness by three different analytical methods for cardiotoxicity assay. Recently, increasing attention has been focused on biofabrication to create biomimetic 3D tissue. Although various tissues can be produced in vitro, there are many issues surrounding the stability and reproducibility of the preparation of 3D tissues. Thus, although many bioprinters have been developed, none can efficiently, reproducibly and precisely produce small 3D tissues (μm-mm order) such as spheroids, which are most commonly used in drug development. The 3D cardiac tissue chips were successfully constructed with a similar number of cells as conventional 2D tissue using a pin type bioprinter, and corresponding drug-induced cardiotoxicities were obtained with known compounds that induce cardiotoxicity. The 3D cardiac tissue chips displayed uniform cell density and completely synchronized electrophysiological properties as compared to 2D tissue. The 3D tissues constructed using a pin type bioprinter as a biofabrication device would be promising tools for cardiotoxicity assay as they are capable of obtaining stable and reproducible data, which cannot be obtained by 2D tissue.